Leveraging immersive virtual reality in e-commerce to foster trust and influence consumer purchase intention: Evidence from the automotive industry - Laakmann, Leon Christopher (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management